ANALYSIS OF THE DEPENDENCE BETWEEN JUMPING TAKEOFF AND ANTHROPOMETRIC INDICATORS OF FEMALE FIGURE SKATERS - Yordanova, Tatiana (Journal of applied sports sciences, 2020)
Jump Elements in figure skating are an integral part of motor activity. One of the conditions for their good performance is great height and length. Criteria for this are the indicators of speed and power qualities. The aim of this research work is to analyze the relationship between anthropometric indicators and those for jumping takeoff of young female figure skaters of the basic level of training. Seventeen female skaters aged 10-14 years old (prepuberty) from ice skating clubs in Bulgaria voluntarily participated in the study. The age of the participants was 10 to 14 years old, which is considered favorable for the development of speed and strength abilities. They were subjected twice to 8 anthropometric measurements and 5 different types of takeoff, conducted in office conditions. To achieve the goal of the survey, the following research methods were used: theoretical analysis and generalization of data in specialized scientific and methodological literature, pedagogical observation, pedagogical testing, anthropometric research methods and methods of mathematical statistics for processing the results of the study. The results showed significant intragroup dependences for the anthropometric and biomechanical parameters for all types of jumps takeoff in the first study and a decrease in the correlation coefficients in the second measurement. The maximum force in all types of jumps increases with increasing indicators of height, weight, length of the lower limbs, chest circumference, shoulder width, while the width of the pelvis does not affect the strength of the takeoff. The height of the jumps with the help of the arms depends on the width of the shoulders - r = .497, and for vertical jump with the hands on the hips - r = .664.